Теоретично – методологічні аспекти вивчення тотожних перетворень раціональних та ірраціональних виразів - Ярова, Оксана Анатоліївна; Романченко, Н. М.; Yarova, Oksana Anatoliivna; Romanchenko, N. M. (Norwegian Academy of Science, 2021)
У статті розглянуто теоретичні та практичні аспекти викладання теми «Вивчення тотожних перетворень раціональних та ірраціональних виразів» у закладах освіти. Узагальнено рекомендації щодо ознайомлення учнів із основними методами розв’язування раціональних та ірраціональних виразів. Розкрито зміст кожного методу, вказано особливості їх використання, проілюстровано застосування кожного методу на конкретних прикладах. Також надано рекомендації щодо викладання даної теми в загальноосвітніх закладах з використанням інноваційних методів.

The article considers the theoretical and practical aspects of teaching the topic "Study of identical transfor mations of rational and irrational expressions" in educational institutions. Recommendations for acquainting stu dents with the basic methods of solving rational and irrational expressions are summarized. The content of each method is revealed, the peculiarities of their use are indicated, the application of each method is illustrated on specific examples. Recommendations for teaching this topic in secondary schools using innovative methods are also provided.
Theoretical - methodological aspects study of identical transformations of rational and irrational expressions
Keywords: математика; вираз; тотожність; нерівності; рівняння; раціональні та ірраціональні вирази; math; expression; identity; inequalities; equations; rational and irrational expressions